Correspondence between stream benthic macroinvertebrate assemblages and ecoregions in northwestern Argentina - Pero, Edgardo Javier Ignacio (2019)
The use of ecoregions to classify stream and river environments has been extensively tested in North America and Europe, but few such studies have been conducted in South America. In this study we tested whether taxonomic richness, composition, and organism abundance within benthic macroinvertebrate assemblages were associated with ecoregions in northwestern Argentina at the genus and family levels. We included 3 ecoregions and their respective subecoregions in this study: the Yungas subtropical cloud forest, the Western Chaco subtropical dry forest, and the Monte xeric shrublands. We used nonmetric multidimensional scaling, analysis of similarity, and rank–abundance curves to assess how assemblages varied among ecoregions and subecoregions. We used principal components analysis to describe how environmental factors varied among sites and regions. Most aspects of invertebrate assemblages were associated with both ecoregions and subecoregions. The structure of the macroinvertebrate assemblages was generally concordant with ecoregional classification at the genus level, although concordance was not evident at the subecoregion level of resolution, especially for family-level data. The segregation of assemblages was most strongly related to environmental variables associated with topography and less strongly related to physiochemical variables. Our results confirm that ecoregions may effectively predict the invertebrate biota inhabiting streams in northwestern Argentina, but it was difficult to delineate discrete assemblages. Future work should assess the effectiveness of modeling approaches that would better account for the gradual changes in assemblage composition that occur along environmental gradients and test how well both classification and modeling approaches partition biotic variation in other parts of South America.